Pengaruh Ukuran Partikel Tepung Kedelai dan Konsentrasi Glukono Delta Lakton (GDL) terhadap Sifat Fisik Tahu Instan - Siti Fauziyyah Masykur; Dede Robiatul Adawiyah; Hoerudin Hoerudin; Purwiyatno Hariyadi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
New process for making instant tofu was developed. Effects of soy flour particle size and GDL concentration on physical properties of instant tofu were studied. Soy beans were ground using a disc mill to produce defatted and undefatted soy flours, and then both were ground using planetary ball mill (PBM) to further reduce their particle sizes. Only defatted soy flour was able to be ground using PBM for 10, 20 and 30 min. Particle sizes were analyzed with laser diffraction technique. Instant tofu was made by adding soy flour to boiling water (15% w/v) and GDL (0.3% and 0.5% of the total mixture), mixed well, followed by stove heating without stirring for 10 min. Physical properties of instant tofu were analyzed using texture profile analyzer, chromameter and scanning electron microscope. Particle size of soy flour had effect on textural properties and microstructure, but not on colour of tofu. Smaller particle size of deffated soy flour (D50= 36.4; 23.8; and 16.1 μm) improved several textural characteristics of the resulting instant tofu; i.e. would increase hardness, chewiness and cohesiveness (with addition of 0.3% GDL) and would increase springiness and chewiness (with addition of 0.5% GDL).